1999
DOI: 10.1063/1.478623
|View full text |Cite
|
Sign up to set email alerts
|

Pump-dump control and the related transient absorption spectroscopies

Abstract: We combine theories of optimal pump-dump control and the related transient probe absorption spectroscopy in order to elucidate the relation between these two optical processes and the possibility of experimental realization. In the weak response regime, we identify the globally optimal pair of pump-dump control fields, and further propose a second-order difference detection scheme to monitor the wave packets dynamics that is jointly controlled by both the pump and dump fields. The globally optimal solution ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…In addition, the time-frequency coherence of light is exploited in optimal control techniques employing shaped pulses, which have been extensively studied theoretically [54][55][56] and experimentally. 57,58 In the present study we seek to generate vibrationally hot population in the ground state, and though infrared pumping has been applied to pump-probe dynamics, 59 we employ the more conventional strategy [60][61][62][63][64] of pumping to an excited state and dumping with a timedelayed pulse of different frequency.…”
Section: Generation Of Vibrationally Hot Population In the Grounmentioning
confidence: 99%
“…In addition, the time-frequency coherence of light is exploited in optimal control techniques employing shaped pulses, which have been extensively studied theoretically [54][55][56] and experimentally. 57,58 In the present study we seek to generate vibrationally hot population in the ground state, and though infrared pumping has been applied to pump-probe dynamics, 59 we employ the more conventional strategy [60][61][62][63][64] of pumping to an excited state and dumping with a timedelayed pulse of different frequency.…”
Section: Generation Of Vibrationally Hot Population In the Grounmentioning
confidence: 99%
“…This observation is consistent with the fact that optimal pumping of the B state of iodine requires a positively chirped pulse. [44][45][46] In Figure 10 we present experimental and theoretical data for the two-dimensional three-pulse FWM where τ ab ) 460 fs and the laser pulses are chirped to 3300 fs 2 . By comparison of the experimental data in Figure 10a with the experimental data in Figure 8a obtained for the same pulse sequence, it is clear that the chirp has introduced ground-state dynamics into the observed signal.…”
Section: A Spectral Information In Femtosecond Three-pulsementioning
confidence: 99%
“…The first two steps in the ͑TD͒ 2 CARS pulse sequence, with their variable time delay, correspond exactly to the pump-dump approach to active control of chemical bond breaking. [7][8][9][10][13][14][15] Early exploration of the pump-dump scheme indicated, that although control of bonding breaking via pump-dump is possible in principle, some variations on the scheme would be required to make it viable for most molecules. 8,77,78 The reason is that the scheme exploits energy picked up by the wave packet on the excited electronic state to break bonds in the ground electronic state.…”
Section: Discussionmentioning
confidence: 99%
“…7,[10][11][12][13][14][15] For example, Shen et al have recently shown that nearly complete population transfer is possible using shaped pump and dump pulses. 15 Nevertheless, an impressive degree of control of ground state wave packet preparation has already been achieved experimentally using only the time delay as the control parameter. Brown et al 16 showed that selective excitation of a ground state wave packet could be achieved even with degenerate wavelength pump and dump pulses by varying only the time delay.…”
Section: Introductionmentioning
confidence: 99%